Modelling falls in Parkinson's disease and normal ageing in mice using a complex motor task. (March 2022) - Jackson, Megan G.; Brennan, Laura J.; Henderson, Emily J.; Robinson, Emma S. J.
Falls resulting from multifactorial deficits are common in both normal ageing and Parkinson's disease. Resultant injuries can lead to increased hospitalisation and excess mortality. As the disease progresses, gait and balance deficits are relatively refractory to dopaminergic treatments suggesting another system is involved. Attentional impairment is a significant risk factor for falls, and disruption to both the cortical cholinergic system and striatal dopaminergic system increases falls in rats undergoing a complex motor task with high attentional load. However, it is unclear whether this translates to mice and whether normal ageing induces similar deficits. In this study, we use a complex motor task to test the effects of acute dopaminergic and cholinergic antagonism using alpha-flupentixol and scopolamine, respectively, in mice. We also test the effects of normal ageing on complex motor performance and whether these changes are sensitive to a clinical dose of the non-steroidal anti-inflammatory Rimadyl. Consistent with previous work, we show that cholinergic but not dopaminergic antagonism impaired task performance. However, a combined approach did not potentiate the deficit beyond observed with cholinergic antagonism alone. We also show that task performance is impaired in aged mice relative to younger controls, and that Rimadyl reduces number of foot slips in an age-specific manner. Overall, these data support prior work showing the importance of the cholinergic system in falls. The studies in aged mice found age-related impairments and a role for inflammation but did not find evidence of an interaction with attentional load, although only one manipulation was tested.